Asymptotic stochastic stability of the stochastic dynamical systems of the random structure with constant delay - Lukashiv, T.O. (Carpathian Mathematical Publications, 2014)
The method of Lyapunov-Krasovskyy functionals is used for the researching of the asymptotic stochastic stability in whole of the stochastic diffusion dynamical systems of the random structure with constant delay, which is under the influence of external impulse disturbances of the Markov’s chain type.